Irrigated soils in region of Rioverde, San Luis Potosí, Mexico - Charcas-Salazar, Hilario; Aguirre-Rivera, Juan Rogelio; Durán-García Héctor Martín (Revista Mexicana de Ciencias Agrícolas, 2018)
The region of Rioverde, San Luis Potosí, Mexico, has 15 132 ha of surface for irrigation; irrigated soils correspond to phaeozems, vertisols, chernozems and solonchaks. For more than 20 years, the laboratory from Rural Development District 130 has accumulated information from analysis of such soils; however no analysis of this data exists which would allow to know variation in physical and chemical properties and soils fertility from the region, as well as repercussions of irrigation on these properties. The aim of this study was to characterize irrigated agricultural soils in such region, based on available laboratory information. It was processed with Excel 97 software for Windows 98 and multiple variable analysis of sorting by main components was applied. Soils are characterized with base to texture, organic matter, reaction, electric conductivity, percentage of interchangeable sodium, available phosphorus and potassium. It is concluded that only when defining percentages of sand, clay and organic matter, the current state of soils from study area and the handling procedures required for its rational exploitation can be known.